Visual and Auditory Learning Styles in Mathematics Learning in the Digital Era for College Students - Takdirmin Takdirmin; Agusalim Juhari (ETDC: Indonesian Journal of Research and Educational Review, 2026)
In the digital era, higher education mathematics faces challenges in aligning complex material with diverse student learning styles. The mismatch between traditional teaching methods and students' sensory preferences often hinders the understanding of abstract concepts within dominant digital platforms. This study aims to analyze and describe the tendencies of visual and auditory learning styles among mathematics education students at Muhammadiyah University of Makassar within digital learning contexts. Employing a qualitative descriptive approach, data were gathered through a Visual-Auditory-Kinaesthetic (VAK) questionnaire, observations of digital learning activities, and in-depth interviews. The data analysis process—comprising data reduction, data presentation, and conclusion drawing—mapped how these learning styles influence student interaction with digital media. The results revealed that students' learning styles are dominated by visual (55%) and auditory (35%) tendencies. Visual learners excelled in interacting with dynamic mathematical software simulations and structured instructional videos, while auditory learners processed concepts more effectively through synchronous discussions on video conferencing platforms and educational podcasts to construct procedural logic. Furthermore, the findings indicate a significant behavioral shift toward multimodal adaptability, where students independently leverage technological features to overcome the limitations of unipolar material. Theoretically, this research contributes to developing adaptive mathematics pedagogical strategies in higher education. Practically, these insights recommend the implementation of Differentiated Learning strategies and a Universal Design for Learning (UDL)-based curriculum that integrates interactive visual elements and clear auditory narratives to minimize cognitive barriers, thereby optimizing students' mathematical literacy.